Rethinking Decentralization in Education in terms of Administrative Problems - Vasiliki Papadopoulou; Ramazan Yirci (Educational Process: International Journal)
The general purpose of this study is to thoroughly examine decentralization in education according to the literature and previous research, and to discuss the applicability of educational decentralization practices in Turkey. The literature was reviewed for the study and findings reported. It has been observed that decentralization in education practices were realized in many countries after the 1980’s. It is obvious that the educational system in Turkey has difficulty in meeting the needs, and encounters many problems due to its present centralist state. Educational decentralization can provide effective solutions for stakeholder engagement, educational financing and for problems in decision making and operation within the education system. However, the present state of local governments, the legal framework, geographical, cultural and social features indicate that Turkey’s conditions are not ready for decentralization in education. A decentralization model realized in the long run according to Turkey’s conditions, and as a result of a social consensus, can help resolve the problems of the Turkish education system.